Treg Therapies Revisited: Tolerance Beyond Deletion - Pilat, Nina; Sprent, Jonathan (Frontiers in Immunology, 2021)
Induction of immune tolerance is the Holy Grail in transplantation medicine and autoimmunity. Currently, patients are required to use immunosuppressive drugs for the rest of their lives, resulting in unwanted side effects and complication from global suppression of the immune response. It is well established that regulatory T cells (Tregs) are critical for the maintenance of immune tolerance towards self-antigens by several mechanisms of immune regulation, in parallel with intrathymic deletion of self-reactive T cells during ontogeny. Therefore, approaches for increasing Treg numbers or function in vivo could provide an all-purpose solution for tolerance induction. Currently, most state-of-the-art therapeutics for treating autoimmune diseases or preventing allograft rejection work either by general immunosuppression or blocking inflammatory reactions and are non-specific. Hence, these approaches cannot provide satisfactory long-term results, let alone a cure. However, in animal models the therapeutic potential of Treg expansion for inducing effective tolerance has now been demonstrated in various models of autoimmunity and allogeneic transplantation. Here, we focus on therapies for increasing the size of the Treg pool by expanding endogenous Treg numbers in vivo or by adoptive transfer of Tregs. In particular, we discuss IL-2 based approaches (low dose IL-2, IL-2 complexes) for inducing Treg expansion in vivo as well as cell-based approaches (polyclonal, antigen specific, or cell engineered) for adoptive Treg therapy. We also mention new questions arising from the first clinical studies on Treg therapy in the fields of transplantation and autoimmunity.